Penggunaan Baju Kebaya Dalam Menumbuhkan Rasa Cinta Tanah Air Pada Anak Usia Dini - Jasmine, Galuh Putri; Wulandari, Hayani (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study seeks to ascertain the efficacy of promoting a deep affection for the nation among young children by consistently donning the traditional kebaya attire on a weekly basis. This research employs a descriptive methodology with a subjective methodology. Information is gathered through polls, perceptions, and different sources like books, articles, and education media. The focal point of the examination is to investigate endeavors in developing a feeling of positive energy in youth. These discoveries act as a kind of perspective for the article composing process. The poll was finished by a sum of 15 respondents. As indicated by the discoveries of the exploration completed at TK Kemala Bhayangkari 11, the regular usage of kebaya as a school uniform is believed to cultivate a patriotic sentiment in young students. Wearing a kebaya provides a direct experience to children so using it regularly can instill a mindset that there is a culture that needs to be preserved by children.